Evaluation of sclerosis in Modic changes of the spine using susceptibility-weighted magnetic resonance imaging. Issue 88 (March 2017) - Böker, Sarah M.; Bender, Yvonne Y.; Adams, Lisa C.; Fallenberg, Eva M.; Wagner, Moritz; Hamm, Bernd; Makowski, Marcus R.
Highlights: SWMR allows a reliable detection of sclerosis in Modic changes. SWI has a better accuracy for detection of sclerosis in Modic changes than T1/T2w MR. By applying SWMR the use of additional CT/radiography can be minimized. Abstract: Purpose: To evaluate the diagnostic performance of susceptibility-weighted magnetic resonance imaging (SWMR) for the differentiation of sclerotic and non-sclerotic Modic changes (MC) of the spine compared to computed tomography (CT) and radiographs. Materials and methods: The Institutional Ethics-Review-Board approved this prospective study in advance. Written consent was obtained from all subjects. SWMR and standard T1/T2 MR of the cervical (n = 21) and/or lumbar spine (n = 34) were performed in 54 patients. 21 patients served as control. 18 patients were evaluated with CT; in all other patients radiographs were available. 67 Modic changes were identified on T1/T2 MR. On SWMR changes were classified as sclerotic and non-sclerotic based on signal intensity measurements. The sensitivity and specificity of SWMR and T1/T2 MR for differentiating between sclerotic and non-sclerotic Modic changes were determined with CT and radiographs as reference standard. Results: On SWMR, signal measurements between sclerotic and non-sclerotic Modic changes differed significantly (p < 0.01). On T1- and T2-weighted MR no significant difference (p > 0.05) was measured. On SWMR, a reliable differentiation between sclerotic and non-sclerotic Modic changes could be achieved, with a sensitivity of 100% and specificity of 95%. In contrast, the combination of T1-/T2-weighted MR yielded a significantly lower sensitivity to detect sclerosis (20%). Conclusion: SWMR allows a reliable detection of sclerosis in Modic changes with a higher accuracy compared to standard spine MR sequences, using radiographs and CT as reference standard.